Asymmetrical Itineraries: Militarism, Tourism, and Solidarity in Occupied Palestine - Kelly, Jennifer Lynn (American quarterly, 2016)
In this essay, the author explores what happens when subjects under occupation attempt to circumvent the archipelagic logic that divides them. In what follows, she shows how, in the context of ever-shrinking Palestinian access to their land, Palestinian tour guides and organizers are using tourism, despite its limitations, to expose the fragmented terrain they have inherited and to attempt to stay anchored to the land they still have. also focus on the deeply and, she argues, deliberately asymmetrical nature of solidarity tourism in Palestine: Palestinian tour guides are guiding tourists through spaces that, often, they themselves cannot go in an attempt to use tourist mobility to highlight their own immobility under military occupation. In this way, this essay focuses on the fragmentation of Palestinian land and the fraught ways in which Palestinian guides and organizers have sought to demonstrate, negotiate, and work against this fragmentation through the unlikely vehicle of tourism.